The Common Causes Leading to Pancytopenia at Tertiary Care Hospital Hossain - Hossain, Mohammad Zaid; Islam, Mohammad Manirul; Salsabil, Masuma Ahmed; Elahi, Quadrat E; Islam, Mazharul; Imran, Md Abdullah Al; Hasan, Pratyay; Rahman, Afsana; Ferdous, Nira; Eva, Israt Zerin; Azad, Khan Abul Kalam (Journal of Dhaka Medical College, 2018)
Pancytopenia is a triad of simultaneous presence of anemia, leucopenia and thrombocytopenia. It is result from a number of disease processes. Both hematopoietic and nonhematopoietic conditions manifest with features of pancytopenia. Methods: This was a cross-sectional study carried out in the Department of Medicine, Dhaka Medical College Hospital between December 2016 to July 2017. We included adult patients of both sexes having age 16 years and above. Criteria for inclusion were persistent pancytopenia on peripheral blood film of more than one week duration. All patients underwent a detailed medical history and full physical examination followed by blood sampling for the investigations. After taking all the aseptic measures and with standard technique the diagnostic bone marrow aspiration and trephine biopsy were done. Results: There were 36 patients with pancytopenia which were included in this study. There were 20 (56%) males and 16 (44%) females with a 1.25:1 male to female ratio and a mean age 47.30 years ± 15.01 SD. The most common complaints were bleeding manifestation (29/36), followed by generalized weakness (27/36) and fever (25/36). Anaemia was the most common (100%) clinical feature followed by jaundice and splenomegaly (6/36). Aplastic anemia was the commonest cause that was observed in 27.78% (10/36) cases followed by Megaloblastic anemia 16.67% (6/36) and erythroid hyperplasia 13.88% (5/36). Conclusion: Aplastic anaemia is leading cause of pancytopenia in this study followed by megaloblastic anaemia and hypersplenism being second and third common causes respectively. Pancytopenia should be suspected on clinical grounds when a patient presents with unexplained anemia, prolonged fever and tendency to bleed. J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 157-161